The Effect of Enterprise Risk Management and Compliance Practices on The Firm Performance of Indonesian Banking Companies - Tewu, M.L. Denny; Bernarto, Innocentius; Suwarno, Suwarno; Lisdiono, Purwatiningsih (Indonesian Journal of Business and Entrepreneurship, 2024)
Enterprise Risk Management (ERM) practices are particularly crucial in this industry to ensure stability and compliance with regulatory requirements. This study examines the effect of ERM on a firm’s operational and financial performances by using two mediating variables of compliance practices and IT strategy. By using a quantitative approach, data was collected through purposive random sampling from 250 bank managers in Jabodetabek, Indonesia. The study found that ERM was found to influence financial and operational performance positively and significantly. Moreover, compliance practices positively and significantly affect both financial and operational performance. IT strategy also has a positive and significant impact on firm performance. In testing the mediating effect, IT strategy partially mediates the relationship between ERM and performance, as do compliance practices. These findings highlight the importance of ERM, IT strategy, and compliance practices in enhancing the performance of banking companies in Indonesia. The findings validate the increasing importance of risk management in the financial landscape in Indonesia. The recognition of the banking sector's complexity and vulnerability to diverse risk types, including credit, market, operational, and regulatory risks, underscores the critical role of risk management practices. Keywords: enterprise risk management, compliance practices, it strategy, financial performance, operational performance